Metastatic nose and paranasal sinus masses – A case series - Latha CS; Begum N; Amaranth SB; Brunda CP; Rao IS; Subrahmanyam C (Journal of Medical and Scientific Research, 2024)
Metastases to the nose and paranasal sinuses are unusual. These tumors are commonly seen in the 4th to 6th decades of life. The clinical presentation may be analogous to that of primary sino-nasal tumors. They usually present with common nasal and ocular symptoms due to which diagnosis may be missed and delayed. Hence, high level of suspicion is necessary for patients with known malignancies presenting with inconsistent or repeated nasal and ocular symptoms. Otorhinolaryngologists should be familiar with these metastases to paranasal sinuses from unusual primary elsewhere in the body, to evaluate and manage these tumors. Retrospective data was collected from the hospital records from 2020-2023. A total 14 cases of sino-nasal malignancies were identified. On further analysis three cases were found to be having distant metastases from primary sites such as kidney, breast and lymph nodes. We are reporting three metastatic malignancies. Each was systematically evaluated, confirming their origin as metastases from other primary sites. They were then managed appropriately.